Meta-analysis of incidence and influencing factors of dry skin in the elderly - XIAO Chunye; PENG Yuxin; WANG Bingyao; FU Guanglei (Yixue xinzhi zazhi)
Objective To systematically evaluate the status and influencing factors of dry skin in the elderly.Methods The PubMed, Embase, Web of Science, CNKI, CBM, VIP and Wan-Fang databases were systematically searched from the establishment of each database to June, 2023. Literature screening, quality evaluation, and information extraction were conducted independently by two researchers, and Meta-analysis of incidence and influencing factors was performed using Stata 17.0 software.Results 19 literatures were included, all cross-sectional studies, including 69,260 elderly patients, of whom 24,580 had dry skin. The results of Meta-analysis showed that the incidence of dry skin in the elderly was 49%[95CI%(36%, 61%)]. The results of subgroup analysis showed that the incidence of dry skin was higher among elderly people in men, from nursing institutions and in the European regions. The prevalence of dry skin in the elderly was also relatively high in the literature with a sample size